SOCIAL UNDERMINING IN THE WORKPLACE. - Duffy, M. K.; Ganster, D. C.; Pagon, M. (Academy of Management Journal, 2002)
An interactive model of social undermining and social support in the workplace was developed and tested among police officers in the Republic of Slovenia. As predicted, social undermining was signi...